How graphic designers rely on intuition as an ephemeral facility to support their creative design process. Issue 4 (2nd October 2021) - de Rooij, Alwin; Dekker, Elise; Slegers, Karin; Biskjaer, Michael Mose
ABSTRACT: Graphic design is a specialized form of creative practice in which images, typography, texts, shapes and other visual elements are created, selected, developed and integrated to form a coherent whole that conveys an intended message and user experience. Anecdotal evidence suggests that intuition is critical in this practice, but exactly how graphic designers rely on their intuition to support their creative design process is poorly understood. Using cultural probes and semi-structured interviews, this qualitative study evidences how twelve professional graphic designers relied on intuition as what we will call an ephemeral facility . Intuition was discerned as a feeling that briefly enters into consciousness and reinforces ongoing, nonconscious decision making, or causes a shift toward conscious reasoning strategies. The study reports how the graphic designers applied intuition throughout their creative design process––for obtaining and selecting information from clients, filling in informational gaps, envisioning a starting point and guiding subsequent actions and evaluations necessary for developing the design. This offers new empirically based insight into the role and relevance of intuition for progressing the creative graphic design process, including the social and material interactions therein.